International Cooperation In The Field Of Internal Affairs Personnel In Uzbekistan - Kholmamatov Faizulla (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
The legal conditions for international cooperation between States are determined by the fact that the international legal order is based on the rule of law and a high level of trust in the system of interstate relations, and the security of the state is interconnected with the security of the entire world community. The main purpose of the article is to prepare law enforcement officers and analyze their activities within the framework of international cooperation. The article will also discuss the benefits of cooperation with international organizations and the results of future strategies in this direction. The study was illuminated on the basis of scientific principles such as historicism, logicism and scientific methods such as inductive and deductive, analysis and synthesis, as well as modern approaches, and its scientific results were summed up according to the principle of unity of theory and practice